Short-term recognition memory correlates with regional CNS expression of microRNA-138 in mice - TATRO, Erick T. (2013)
OBJECTIVES: We hypothesized that microRNA (miR) expression may be involved in memory function because they control local protein translation at synapses and dendritic spines. DESIGN: Case-control animal study. METHODS: We assessed the miR repertoire in the hippocampus of young, 6-month old (n = 18), mice compared to aged, 26-month old (n = 23), mice and compared miR quantity to memory scores as determined by the novel object recognition task (NORT). We performed a histological brain regional analysis of miR-138, APT1 mRNA, and APT1 protein. RESULTS: We found that higher miR-138 in the mouse hippocampus is correlated with better memory performance. We also found that acyl protein thioesterase 1 (APT1), a depalmytoylation enzyme expressed at dendritic spines whose translation is controlled by miR-138, mRNA is increased in the mouse hippocampal CA1 and dentate gyrus in aged mice compared to young, but not in mice with memory impairment. We found APT1 protein distribution to be lower in cells with high miR-138 expression. CONCLUSIONS: These results suggest that increased miR-138 is associated with better memory and increased APT1 gene transcription occurs with aging. The role of miR-138 and APT1 protein function in memory and aging warrants further investigation.